Derivative Words Scraping of Every Quranic Root Word from the Quran Corpus Web using Python to Support the Quranpedia Project - Idzhari Syaeful Ma'mun -; Eko Darwiyanto; Moch. Arif Bijaksana (STMIK Budi Darma, 2023)
The Qur'an, as a guide to life for Muslims, has given birth to various disciplines such as tafsir science, fiqh science, hadith science, nahwu science, and balaghah science. However, the limited number of websites on learning and understanding the Qur'an is a problem that can hinder Muslims from exploring the contents of the Qur'an. To overcome this problem, the Quranpedia project was initiated. Quranpedia is a web-based application designed to resemble Wikipedia in providing in-depth explanations of derivative words in the Qur'an. Using the